Learning Al-Qur'an Using Asy-Syifaa Method at Islamic Pre-Elementary School - Muh. Hanif; Rahma Kemala Dewi; Abu Dharin; Florian Pohl (IAI Ma'arif NUMetro Lampung, 2023)
Islamic Pre-Elementary school or Taman Pendidikan Al-Qur'an (TPQ) was a non-formal education in the field of the Islamic religion to create a generation that was Al-Qur'an and has good morals. At TPQ, various methods of learning the Qur'an were used to assist the learning of the Al-Qur'an to teach effectively. The article aimed to describe how the Asy-Syifaa method was implemented in the Al-Qur'an learning process at TPQ MNU Miftahul Ulum. In the implementation of it's learning, several activities start from opening, core, and closing. This research included  qualitative research by using the collecting data of observation and interviews. This research is conducted at TPQ MNU Miftahul Ulum, Kalijambe Village Tarub District, Tegal Regency. The result indicates that the application of the Asy-Syifaa method in learning at TPQ is considered much more effective, which consists of 4 volumes in the Al-Qur'an learning process. The learning stages are opening in class, individual, classical, and closing. Three kinds of evaluation are applied: daily evaluation, volume increase evaluation, and final evaluation of learning the Qur'an. Keywords: Asy-Syifa Method, Al-Qur'an Learning Process, Asy-Syifaa Learning Method